A Modern Reading of the History of Taxation in Ancient Rome - Kalchev, Emil (Economy and Business Yearbook, 2022)
With the entrance of the modern world into economic and political difficulties, the question of the financial support to population and business by the state is much more acute. A major financial source for states, taxes in turn have a strong influence on the behavior of citizens and companies, which are generally opposed to their increase. What is the historical attempt to resolve this contradiction? The history of taxes in Ancient Rome, the progenitor of modern European and Western civilization, shows us that taxes are not just a source of financing, but also a basic structural element of the state and society. Their significant growth led in antiquity not only to riots, riots and bloodshed, but also to serious changes in the construction of the Roman economy and society. At the same time, the observance of the principles of fairness of taxes and the control of their collection prove to be key for their functioning within the economy and society. The ultimate rise in taxes led to a stateregulated economy in Rome, i.e. to the prototype of real socialism, and the end of the Roman Empire. This is the end of the road for state support. Will the modern world catch up with it again?